International humanitarian law - Eishan Jan, Mohammad Naqib; Lawan Haruna, Abdulrashid (IIUM Press, 2015)
This book is written not because of any foreseen break of armed conflict, but armed conflict is an inevitable phenomenon in human and international relations since despite the United Nations Charter prohibition on the use of force in international relations, war still exist. Hence, there is need to have law that regulates conduct in time of armed conflict. International humanitarian law (IHL) being the law of armed conflict has to be disseminated to the entire society through a comprehensive medium that everyone can understand and appreciate. IHL provisions that are mainly contained in the Geneva Conventions and the Additional Protocols have spelt out the basic rules concerning conduct of parties to an armed conflict and the limitations on the use of means and methods of warfare. Recent trends in multi-faceted modern conflicts and the changing phases of such conflicts have been of tremendous concern for IHL experts and students. In view of this, the book considers certain pertinent issues that border on the main idea of IHL, which is to regulate conduct of belligerents in armed conflict. Issues such as the contemporary trans-border conflicts and the recent novel global agenda on war against terrorism, which have posed a serious challenge to the comprehensive understanding and application of IHL. Other issues include the flagrant abuse of the principles safeguarding civilians and civilian objects in time of armed conflict, as well as the failure to make violators of the principles to assume full responsibility of their deeds by subjecting them to penal repression. It also considers recent armed conflicts that happened or happening around the world and how they affect or impact on the existing rules of IHL. Having considered the content of most IHL textbooks, this book attempts to give a simple and comprehensive position of the law and its practical applicability to the current events and IHL related issues, for the purpose of easy understanding of the law and how it functions in a globalized society. As an additional distinctive feature, the book considers the Islamic perspective of humanitarian law by examining the relationship between Islamic jus ad bellum vi and jus in bello, the prohibited means and methods of warfare, protection of civilians in time of armed conflict and the position of civilian objects. It discloses the adequacy of humanitarian considerations and humane principles available under Islamic jus in bello, which refutes the claims that Islamic law does not protect civilian and civilian objects in time of armed conflict. Therefore, this book is indeed a relevant material and a good asset for students and IHL practitioners as it provides them with comprehensive and aptly researched position and application of IHL. Prof.